MINDP-MAPPING AS A TOOL OF ORGANIZING SELF-DEPENDENT COGNITIVE ACTIVITY OF CADETS ON PHYSICS (Journal of Information Technologies in Education (ITE), 2012)
The article deals with the possibility of using mind-mapping in organizing of self-dependent work of cadets on physics and suggested examples of tasks for their implementation.
Keywords: associative map; concept-map; diagram of connections; map of knowledge; mental map; mind-mapping; radiant thinking; self-dependent work